KONTRIBUSI DAYA LEDAK OTOT TUNGKAI DAN KELENTUKAN TUBUH TERHADAP KEMAMPUAN HEADING PADA PEMAIN SEPAKBOLA TIM SMPN 2 BUKIT BATU - Muhammad Sani; Saripin Saripin; Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT, Problems in this study originated from the observation of the authors at the time of friendly matches and tournaments, followed by a team of SMPN 2 Bukit Batu, low ability Heading students SMPN 2 Bukit Batu caused by several factors, including: low physical ability, especially the lack of explosive power leg muscle making it less strong repulsion in the body do make the leap. The purpose of this study was to determine how much explosive power leg muscle contributes to the ability of heading at SMPN 2 Bukit Batu. This type of research is correlational. Population in this research is the students of SMPN 2 Bukit Batu, amounting to 35 people using the total engineering side where all the population sampled, to obtain research data used vertical jump and heading test. Data were analyzed with a simple product moment, to determine the contribution of used frequency determinant. Based on data analysis found that the results obtained from the explosive power leg muscle had no significant relationship with the ability Heading students SMPN 2 Bukit Batu, characterized by the results obtained by the rhitung (0494)> rtabel, (0334) and has contributed Kp = r2 (0.4942) x100% = 24%.Keywords : Explosive Power Leg Muscle, Heading,, Football